Faktor-Faktor Yang Mempengaruhi Perilaku Adaptif Anak Usia Dini - Rizqiyah Ratu Balqis (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Adaptive behavior is one of the abilities that must be possessed by every individual to live a good social life. Adaptive behavior will influence children's successful in their social life. Therefore, this paper aims that influence the adjustment process include: physical condition, personality, education, environment, religion and culture.to reveal the various factors that can influence early childhood behavior. The factors